Apakah Financial Leverage dan Kepemilikan Institusional Mempengaruhi Tindakan Perataan Laba? - Lestari, Dwi Indah; Aprilia, Dhea (JPAK : Jurnal Pendidikan Akuntansi dan Keuangan, 2020)
This study aims to determine the effect of financial leverage and institutional ownership upon income smoothing. We hope that this research can contribute to filling the research gap because the previous researches show an inconsistent result. This research is conducted in manufacturing companies in Indonesia Stock Exchange from 2016-2018. We are using secondary data in a form of audited financial report that can be accessed in www.idx.co.id. Quantitative method is applied as a method of this research, with a total sample of 246 units. The result shows that, partially, financial leverage has no effect on income smoothing and institutional ownership has a negative impact on income smoothing. While simultaneously, financial leverage and institutional ownership affect income smoothing.